Validation and implementation of principles of the Integrated Pest Management concept - sustainability and current challenges in pest endemic pulse bowl of India - SHARMA, O P; RACHAPPA, V; YELSHETTY, SUHAS; NAIK, HARISCHANDRA; GOPALI, J B; SAINI, MANISH RANJAN (The Indian Journal of Agricultural Sciences, 2023)
Insect pests and vascular diseases are the major constraints to pigeonpea production in Karnataka and primarily responsible for lower productivity. There is no substantial host plant resistance to key insect pests in currently adopted cultivars, however effective utilization of other components of pest management led to development of various integrated pest management (IPM) to minimize yield losses and protect the environment. In present studies, it is a total “system approach” to sustainable pest management involving seed treatment with microbials, synchronized sowing, modification in landscape and application of need-based pesticide spray. Spray schedule was combined with online pest monitoring system for the plant protection related advisories for the target region. The resultant IPM package implemented through farmer-managed operational scale plots and compared with non-IPM (normal farmer practices) across 7 taluks of Gulbarga district for 4 years (2010–2013 seasons). A total of 2197 farmer-managed demonstrations were conducted, giving a 5–104% yield advantage (district means) of IPM over farmers’ practice. Pest incidence data in IPM vis-à-vis non-IPM clearly indicates that pest can be managed by adopting IPM technology. Number of spray of pesticides could be reduced from 6 to 4. Pesticide residue analysis for 102 chemical pesticides for representative soil, water and grain samples drawn from IPM as well as non-IPM (farmers’ practice) fields, indicates their presence within the prescribed limits. Grain yields in IPM plots were generally 15–20% higher than in FP. Even with all the available inputs, the production is subject to residual production risk due to abiotic constraints (rainfall), diseases and insect pests, which often large farmers are able to bear. Here in present studies it has been clearly demonstrated that strategies are friendly and adoptable by the small and marginal farmers. Effective implementation of IPM practices by participating farmers demonstrated that remunerative and reliable yields could be obtained in this pest-prone environment and helps mitigate climate induced threat to agricultural development having relevance to other pigeonpea growing regions prone to similar pest pests.